Sam Houston Boy Chieftain - Stevenson, Augusta (Bobbs-Merrill Company, Inc. New York, 1962)
A biography of the man who helped make Texas a part of the United States, emphasizing his boyhood in Virginia and his friendship with the Cherokee Indians.
Keywords: Houston, Sam -- 1793-1863